SEMI OTOMASI MESIN PENYEIMBANG - Abidin, Zainal; Bagiasna, Komang; Purwowinarwan, Sigit; Iskandar, Ishak S (Mesin, 1996)
This paper presents research on the development of semi automation technique for balancing machines. Using this technique, rotational speed of rotors, data acquisition process, and amplitude and phase of vibration calculations could be performed by a computer. Consequently, faster and more accurate balancing process can be achieved. The effectiveness of the proposed control method was verified using experimental results. In this test, the rotor speed was measured by and compared to the results obtained from software, a digital oscilloscope, a digital tachometer and a Multi Channel Spectrum Analyzer M/ISA). Furthermore, to verify the accuracy of amplitude and phase calculations, the values obtained from the developed software were compared to those from analytical results obtained from MSA.